A Comparative Study on Phytochemical Screening and Antioxidant Activity of Aqueous Extract from Various Parts of Bauhinia purpurea - Tin Mar Htay; Kyi Kyi Sann; Hazwan Haini (Bioactivities, 2023)
In this study, we conducted a comparative investigation into the phytochemical screening and antioxidant activity of aqueous extracts from various parts of the Bauhinia purpurea plant, including leaf, flower, stem bark, and root. The qualitative analysis was performed to screen the phytochemical content of each extract, followed by quantitative analysis to determine the total phenolic and total flavonoid contents. Our findings revealed that different parts of the B. purpureaplant yielded distinct natural products upon extraction. Both the leaf and flower extracts contained alkaloids, flavonoids, saponins, carbohydrates, polyphenols, and phenolics. On the other hand, the aqueous extracts of the stem barks and rootparts of B. purpurea only contained alkaloids, flavonoids, and phenolics. Consistent with the phytochemical assay, the flower extract exhibited the highest total phenolic content (40.14 ± 0.65 µg/mL GAE) and the highest flavonoid content (387.57 ± 0.63 µg/mL CE) compared to the other parts. Consequently, the flower extract displayed the highest antioxidant activity (51.76 ± 0.32%) with DPPH radical assay, closely approaching the antioxidant activity of ascorbic acid (70.54 ± 0.51%), which served as the positive control. This significant finding highlights the potential of the B. purpurea flower as a potent source of antioxidant agents for future applications.